Correlações entre zona de estiramento e tenacidade à fratura para aço 15-5PH - Silva, Ikaro Amorim e [UNESP] (2016)
This work includes a study on the stretch zone and the influence of the toughness conditions at fracture in size and appearance. It was done a literature review about material properties, fracture mechanics concepts, definitions and formation of stretch zone, importance of tenacity for structural calculation, methods and standards to measure the toughness of metallic material fracture and presents the method used in microscopy. After the literature review were carried out identification and measurements of stretch zones of proof bodies were made through confocal optical microscopy and then analyzed the results in order to find relationships between the values obtained with the theory